Studi Perkembangan Pariwisata di Pantai Melasti Desa Ungasan, Kecamatan Kuta Selatan, Kabupaten Badung - Langu, Bellawasti Inna Ringu; Sunarta, I Nyoman (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
This study examines the study of tourism development and the determination of development positions in Melasti Beach. Therefore related to the development of tourism, this study describes attractions, facilities, number of visits and community involvement and using the guidelines of the Butler theory.The qualitative methods was used with qualitative and quantitative types data. Data sourcing from the primary and secondary data. Data collection was carried out by observation, interviews and the library research. The technique data analysis is the qualitative descriptive. This research find that the Melasti beach experienced a significant tourism development and based on the butler theory the Melasti beach was in the second stage namely involvement. Keyword: tourism development, the position of tourism